2012
DOI: 10.1002/ptr.4749
|View full text |Cite
|
Sign up to set email alerts
|

Formulas Used by Tibetan Doctors at Men‐Tsee‐Khang in India for the Treatment of Neuropsychiatric Disorders and Their Correlation with Pharmacological Data

Abstract: The aim of the present study was to identify formulas used at Men-Tsee-Khang (Tibetan Medical and Astrological Institute), India, for the treatment of neuropsychiatric disorders and to compare the Tibetan usage of particular ingredients with pharmacological data from the scientific database. Using ethnographic methods, five doctors were selected and interviewed. A correlation was observed between central nervous system disorders and rLung, one of the three humors in Tibetan medicine, which imbalance is the sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…Nutmeg has been used externally to treat skin infections, rheumatism and paralysis (Khan & Abourashed 2010). Other interesting uses for nutmeg include the treatment of psychological disorders (Antonio et al 2013), and as a cheap substitute for marijuana especially among teenagers, sailors and prison inmates (Weil 1966). …”
Section: Introductionmentioning
confidence: 99%
“…Nutmeg has been used externally to treat skin infections, rheumatism and paralysis (Khan & Abourashed 2010). Other interesting uses for nutmeg include the treatment of psychological disorders (Antonio et al 2013), and as a cheap substitute for marijuana especially among teenagers, sailors and prison inmates (Weil 1966). …”
Section: Introductionmentioning
confidence: 99%
“…2 All these species have been used as folk medicine for many years. 3,4 Owing to their interesting pharmacological profile, the chemical constituents of M. f ragrans and M. dactyloides have been studied extensively. This has led to the isolation of various compounds including diarylnonanoids, which are referred to as malabaricones.…”
mentioning
confidence: 99%
“…Four species of the Myristica genus, M. ceylanica , M. dactyloides , M. malabarica , and M. fragrans , are found in Sri Lanka and the southern part of India . All these species have been used as folk medicine for many years. , Owing to their interesting pharmacological profile, the chemical constituents of M. fragrans and M. dactyloides have been studied extensively. This has led to the isolation of various compounds including diarylnonanoids, which are referred to as malabaricones. Among these natural products, malabaricones B and C displayed various interesting biological activities including nematocidal, anti-inflammatory, antioxidant, anti-quorum sensing, antimicrobial, antifungal, antipromastigote, acetylcholinestearase inhibitory, antiproliferative, and cytotoxicity effects against human cancer cell lines, antihypertensive effects, and gastroprotective properties against stomach ulceration .…”
mentioning
confidence: 99%
“…In another study, adipose tissue reduction was shown in rats that were given a nutmeg extract which warrants further investigation to examine the effects of nutmeg on weight and diabetes [15]. Recent studies have also shown that nutmeg may act as a CNS stimulant, psychotropic, aphrodisiac and anti-inflammatory agent [11,16-19]. For example, Baker et al .…”
mentioning
confidence: 99%
“…In addition to its use as a kitchen spice, nutmeg has traditionally been used to increase appetite, improve digestion, and to manage such GI conditions as colic, nausea, diarrhea, and flatulence [1,3,10]. Traditional Chinese medicine, Tibetan medicine, and Ayurveda employ multi-ingredient formulas to treat neuropsychological disorders, and many formulas contain nutmeg as a common ingredient [11]. Various online documents and forums present controversial discussions on the psychotropic effects of nutmeg, which is regarded by some recreational drug users as a cheap marijuana substitute [12,13].…”
mentioning
confidence: 99%